2008
DOI: 10.1172/jci32899
|View full text |Cite
|
Sign up to set email alerts
|

Eya4-deficient mice are a model for heritable otitis media

Abstract: Otitis media is an extremely common pediatric inflammation of the middle ear that often causes pain and diminishes hearing. Vulnerability to otitis media is due to eustachian tube dysfunction as well as other poorly understood factors, including genetic susceptibility. As EYA4 mutations cause sensorineural hearing loss in humans, we produced and characterized Eya4-deficient (Eya4 -/-) mice, which had severe hearing deficits. In addition, all Eya4 -/-mice developed otitis media with effusion. Anatomic studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 45 publications
2
77
0
Order By: Relevance
“…Unfortunately, data to support this possibility have yet to be reported. As reported in this issue of the JCI, Depreux et al (6), in the process of investigating hearing loss in Eya4 -/-mice, found that these mutant animals had OME. The existence of a genetic basis for OME has been previously suggested, as the incidence of OME has been shown to be higher in twin siblings (3); but in their current study Depreux et al propose that deletion of a specific gene, Eya4, causes OME (6).…”
Section: A Genetic Basis For Omementioning
confidence: 83%
See 1 more Smart Citation
“…Unfortunately, data to support this possibility have yet to be reported. As reported in this issue of the JCI, Depreux et al (6), in the process of investigating hearing loss in Eya4 -/-mice, found that these mutant animals had OME. The existence of a genetic basis for OME has been previously suggested, as the incidence of OME has been shown to be higher in twin siblings (3); but in their current study Depreux et al propose that deletion of a specific gene, Eya4, causes OME (6).…”
Section: A Genetic Basis For Omementioning
confidence: 83%
“…The study by Depreux et al (6) shows that the Eya4 gene may play a critical role in structuring the ET and that immature development of these structures predisposes Eya4 -/-mice to OME. While the degree of conductive hearing loss in the Eya4 -/-mouse is unknown, and may be overshadowed by inner-ear defects, the degree of similarity between the OME dysmorphology of the middle ear observed in the mutant mouse and that observed in humans is nevertheless remarkable.…”
Section: A Genetic Basis For Omementioning
confidence: 99%
“…Moreover, since EYA4 is reported to form homodimers (Schönberger et al, 2005), truncated proteins may have a dominant negative effect on the full-length EYA4. Recently, Eya4-deficient mice have been reported to exhibit abnormal middle ear cavities and Eustachian tube dysmorphology (Depreux et al, 2008). However, fine structural abnormalities of the cerebrum have not been investigated.…”
Section: E953 Discussionmentioning
confidence: 99%
“…There are multiple factors involved in this process. It has been reported that anatomic abnormality, genetic predisposition, and middle ear immunity play important roles in the pathogenesis of COM [3][4][5][6][7]. To make middle ear infection chronic, there must be some compromised innate or adaptive immunity in the middle ear mucosa.…”
Section: Introductionmentioning
confidence: 99%